Mobile application for individual identification as social relationship sustainability development in community and society: 'Know You App' / Nurul Aishah Abd Rahman ... [et al.] - Abd Rahman, Nurul Aishah; Mohd Latib, Farah Wahida; Jaafar, Mohd Risham; Muhamad, Noor Safwan; Bachok, Mohd Fairuz (Universiti Teknologi MARA, Perak, 2020)
KNOW YOU APP' was developed for the public to properly identify individuals. An individual in any organization can be identified by simply typing the organization and the individual's name; consequently, the detailed biodata and the photo of that individual will be displayed. Additional, this app include the recording of meetings so that in the future when they meet again, these records can provide information like when, where and why they met before. 30 respondents were selected from among the UiTM Pahang staff to provide feedback as users and by using SPSS analysis, a very positive feedback was found with 95% respondents gave a mean score of 4.0 to 5.0 to show the effectiveness level of this mobile application.